Convexity of Certain q-Integral Operators of p-Valent Functions. (12th May 2014) - Selvakumaran, K. A.; Purohit, S. D.; Secer, Aydin; Bayram, Mustafa
Abstract : By applying the concept (and theory) of fractional q -calculus, we first define and introduce two new q -integral operators for certain analytic functions defined in the unit disc 𝒰 . Convexity properties of these q -integral operators on some classes of analytic functions defined by a linear multiplier fractional q -differintegral operator are studied. Special cases of the main results are also mentioned.